Review: Semitic Linguistics: The State of the Art at the Turn of the 21st Century - Lipiński, Edward (Journal of Semitic studies, 2006)
Semitic Linguistics: The State of the Art at the Turn of the 21st Century Shlomo Izre'el . (Israel Oriental Studies XX). Eisenbrauns, Winona Lake 2002. 535. Price: $59.50 . ISBN: 1-57506-059-0